The Development of 3D Bovine Intestinal Organoid Derived Models to Investigate Mycobacterium Avium ssp Paratuberculosis Pathogenesis - Blake, Rosemary; Jensen, Kirsty; Mabbott, Neil; Hope, Jayne; Stevens, Joanne (Frontiers in Veterinary Science, 2022)
Mycobacterium avium subspecies paratuberculosis (MAP) is the etiologic agent of Johne’s Disease, a chronic enteritis of ruminants prevalent across the world. It is estimated that approximately 50% of UK dairy herds are infected with MAP, but this is likely an underestimate of the true prevalence. Infection can result in reduced milk yield, infertility and premature culling of the animal, leading to significant losses to the farming economy and negatively affecting animal welfare. Understanding the initial interaction between MAP and the host is critical to develop improved diagnostic tools and novel vaccines. Here we describe the characterisation of three different multicellular in vitro models derived from bovine intestinal tissue, and their use for the study of cellular interactions with MAP. In addition to the previously described basal-out 3D bovine enteroids, we have established viable 2D monolayers and 3D apical-out organoids. The apical-out enteroids differ from previously described bovine enteroids as the apical surface is exposed on the exterior surface of the 3D structure, enabling study of host-pathogen interactions at the epithelial surface without the need for microinjection. We have characterised the cell types present in each model system using RT-qPCR to detect predicted cell type-specific gene expression and confocal microscopy for cell type-specific protein expression. Each model contained the cells present in the bovine ileum and were therefore representative of the bovine gut. Exposure of the three model systems to the reference strain MAP K10, and a recent Scottish isolate referred to as C49, led to the observation of intracellular bacteria by confocal microscopy. Enumeration of the bacteria by genome copy number quantification, indicated that K10 was less invasive than C49 at early time points in infection in all model systems. This study shows that bovine enteroid-based models are permissive to infection with MAP and that these models may be useful in investigating early stages of MAP pathogenesis in a physiologically relevant in vitro system, whilst reducing the use of animals in scientific research.